Exercise Outcomes in Childhood Obesity-Related Inflammation and Oxidative Status - Estébanez, Brisamar; Huang, Chun-Jung; Rivera-Viloria, Marta; González-Gallego, Javier; Cuevas, María J. (Frontiers in Nutrition, 2022)
Childhood obesity is identified as one of the major public health issues to increase the risk for cardiometabolic diseases and related complications in adulthood. The literature has supported inflammation and oxidative stress as the primary underlying mechanisms involved in the pathogenesis of obesity-related diseases. Epidemiological evidence consistently shows the benefits of physical activity in the improvement of obesity-mediated inflammation and oxidative stress status. In this narrative mini-review, the available scientific evidence on the potential effects of exercise in alleviating these susceptibilities in childhood obesity will be assessed.